Предмет: Математика, автор: kris5540

Решение уравнения :
-2х-4=3х
-5х-2=-3х
5х-6=-3х
-4х+5=х
х-2=-3х
-4х-2=-3х​

Ответы

Автор ответа: alexandra2132
1

-2х-4=3х

-2х-3х = 4

-5 х = 4

-х = 4/5

х = -4/5

х = - 0.8

-5х-2=-3х

-5х +3х = 2

-2х = 2

- х = 1

х = -1

5х-6=-3х

5х +3х = 6

8х = 6

х = 6/8

х = 0.75 (или 3/4)

-4х+5=х

-4х -х = - 5

-5х = -5

х = 1

х-2=-3х

х +3х = 2

4х = 2

х = 2/4

х = 1/2

х = 0.5

-4х-2=-3х

-4х+3х = 2

-х = 2

х = -2

Похожие вопросы
Предмет: Математика, автор: Аноним